The Quality of Beef on Traditional Market in Poncokusumo Subdistricts Malang Regency - Dedes Amertaningtyas (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2012)
ABSTRACT The purpose of this study was to determine the physical quality of beef sold by traders fresh beef, namely moisture content, pH, water holding capacity (WHC), cooking loss or shrinkage cooking and texture or tenderness compared with the literature on the quality of fresh beef eligible . The results showed that the physical quality of fresh beef sold in the traditional market traders Poncokusumo District of Malang Regency still eligible or safety standards for the fresh cow consumption. The beef has moisture content of 76.53 %, pH of 5.62, cooking loss or shrinkage of 24.60 % ripe, WHC (water holding capacity) 37.10 % and 23.84 N texture or tenderness. Key words: physical quality of beef , traditional marketABSTRACTThe purpose of this study was to determine the physical quality of beef sold by tradersfresh beef, namely moisture content, pH, water holding capacity (WHC), cooking loss orshrinkage cooking and texture or tenderness compared with the literature on the quality offresh beef eligible . The results showed that the physical quality of fresh beef sold in thetraditional market traders Poncokusumo District of Malang Regency still eligible or safetystandards for the fresh cow consumption. The beef has moisture content of 76.53 %, pH of5.62, cooking loss or shrinkage of 24.60 % ripe, WHC (water holding capacity) 37.10 % and23.84 N texture or tenderness.Key words: physical quality of beef , traditional market